Psychological distress of mental health workers in a pandemic context and associated factors: a cross-sectional study - Stander, Ana Luisa Camachi [UNESP]; de Oliveira, Márcia Aparecida Ferreira; Claro, Heloísa Garcia; de Andrade Boska, Gabriella; de Mattos Cerioni Silva, Júlia Carolina; Barbosa, Guilherme Correa [UNESP] (Escola de Enfoermagem Aurora de Afonso Costa, 2024)
Objective: To analyze the psychological distress of mental health workers in a pandemic context and identify associated factors. Method: A cross-sectional study was conducted with 108 workers from four mental health services in a municipality in the interior of São Paulo. Data was collected online between October and December 2020 through a sociodemographic questionnaire and the Self Report Questionnaire-20 (SRQ-20) scale. The data were analyzed using descriptive statistics and multiple linear regression of ordinary least squares to analyze the factors associated with the variation in the scale score. Results: The workers had a high average on the SRQ-20 scale (15.07), indicating significant psychological distress. Receiving psychological and/or psychiatric support during the COVID-19 pandemic was associated with reducing this distress, with an average reduction of three symptoms assessed by the scale. Conclusion: Mental health support for workers in the pandemic context can be an important coping strategy associated with reducing psychological distress.
Sofrimento psíquico de trabalhadores de saúde mental em contexto pandêmico e os fatores associados: estudo transversal
Keywords: Health Personnel; Mental Health; Pandemics